2020
DOI: 10.3390/jcm9030632
|View full text |Cite
|
Sign up to set email alerts
|

Do Knee Pain Phenotypes Have Different Risks of Total Knee Replacement?

Abstract: Pain is the main impetus for osteoarthritis (OA) patients to seek healthcare including joint replacement. The pain experience in OA is heterogeneous and affected by factors across multiple domains—peripheral, psychological, and neurological. This indicates the existence of homogenous subgroups/phenotypes within OA patients with pain. We recently identified three pain phenotypes using a wide spectrum of pain-related factors, including structural damage on magnetic resonance imaging (MRI), emotional problems, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Real-time access to big data during the clinician-patient encounter provides an opportunity to make the best treatment decisions in individual situations [ 4 ]. These aggregate datasets can be transformed to individualized information to guide shared decision-making between patients and clinicians in arthritis care [ 5 ]. Efforts to transform comprehensive real-world evidence to individualized, actionable information require health systems to develop best practices for integrating PROs with real-world data to support shared decision-making [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Real-time access to big data during the clinician-patient encounter provides an opportunity to make the best treatment decisions in individual situations [ 4 ]. These aggregate datasets can be transformed to individualized information to guide shared decision-making between patients and clinicians in arthritis care [ 5 ]. Efforts to transform comprehensive real-world evidence to individualized, actionable information require health systems to develop best practices for integrating PROs with real-world data to support shared decision-making [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…White et al [15] believes that perioperative education can well improve the postoperative knee exion, 72% of the patients with good perioperative education can kneel with their affected knees 1 year after the surgery. The acceptance of perioperative knowledge, such as eliminating fear, avoiding rough training, controlling training methods and time, and comprehensive pain control, largely depends on the patient's EL [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pain is the most common symptom complained by patients [27] . The preoperative patient's psychology is an important factor affecting the pain of patients after TKA [16,28] . It is still a di culty that how to identify better whether patients are at high risk of complications owing to psychiatric disorders [13] .…”
Section: Education Level Could Also Affect the Rehabilitation Via Pat...mentioning
confidence: 99%
“…Measurements of knee structural abnormalities on MRI, emotional problems, number of painful sites, BMI, sex, education level, and comorbidities, which were measured by trained observer(s) or self-report questionnaires at baseline, were used to identify pain phenotypes. The details of each measurement have been described elsewhere [ 25 , 26 ]. In brief, each participant had an MRI scan on their right knee in the sagittal plane on a 1.5-T whole body MR unit (Picker, OH) using a commercial transmit–receive extremity coil.…”
Section: Methodsmentioning
confidence: 99%
“…Our recent study has identified three distinctive knee pain phenotypes by considering a broad range of pain-related factors, including structural abnormalities on magnetic resonance imaging (MRI), emotional issues, body mass index (BMI): Class 1: high prevalence of emotional problems and low prevalence of structural damage (38%); Class 2: high prevalence of structural damage and low prevalence of emotional problems (17%); Class 3: low prevalence of emotional problems and low prevalence of structural damage (45%) [ 25 , 26 ]. Further, pain severity and number of painful sites were found to be different between the classes/subgroups [ 26 ].…”
Section: Introductionmentioning
confidence: 99%